Severe human Bocavirus 1 respiratory tract infection in an immunodeficient child with fatal outcome - Tabatabai, Julia; Fakhiri, Julia; Meyburg, Jochen; Linse, Kai-Philipp; Grimm, Dirk; Schnitzler, Paul (The pediatric infectious disease journal, 2019)
We report a case of lower respiratory tract infection with human bocavirus 1 (HboV1) in an immunodeficient 6-month-old boy leading to respiratory failure with fatal outcome. Polymerase chain reaction of serum/tracheal secretions revealed exceptionally high HboV1-DNA levels and immunoassays showed seroconversion indicating an acute primary HboV1 infection. All assays for other pathogens were negative, strongly suggesting that HboV1 was the causative agent in this case.